The Feral Child - Golden, Che (London Quercus, 2012)
They take human children and leave changelings in their place ... stolen children go into the mound and we can't follow.' Her parents dead, Maddy is sick of living in Ireland, sick of Blarney and sick of her cousin Danny, one of the nastiest people you could meet this side of an Asbo. Mad as hell one evening, she crawls inside the grounds of the castle, the one place she has always been forbidden to go. Once inside, she is chased by a strange feral boy, who she suspects is one of the faerie: cruel, fantastical people who live among humans and exchange local children for their own. When the boy returns to steal her neighbour Stephen into his world, Maddy and her cousins set off on a terrifying journey into a magical wilderness, determined to bring him back home. To do so, they must face an evil as old as the earth itself ... Che Golden has created a dashing adventure that interweaves Maddy's life in modern-day Ireland with a scintillating magical world
Keywords: Changelings -- Ireland -- Children's stories